DEFENSE TO SURVIVE OF SYDNEY WELLS IN DAVID MOREAU'S "THE EYE" MOVIE: A PSYCHOANALYTIC APPROACH - RETISENT, HANUM GESIK (2010)
This research is aimed to analyze the structural elements of The Eye movie by David Moreau's such as character and characterization, plot, point of view, style and theme based on psychoanalytic perspective. This research is a qualitative research. The data are taken from document analysis. The object of the study of the research is to analyze the structural elements of the movie and to analyze the psychoanalytic defense mechanism in surviving dealing with the ghost vision on her sight reflected in The Eye movie. The results of study as follows; the character and characterization of the actors. From Lionsgate and Paramount Vantage, The Eye is based on the 2002 Asian horror film of the same name written by Jo Jo Yuet-chun Hui, Oxide Pang and Danny Pang and directed by the Chinese filmmaking duo Danny Pang and Oxide Pang. The film, which was an international hit, caught the attention of C/W Productions, who bought the rights for an American remake. Then based on the defense mechanism psychoanalytic approach, defense can happen if there is a threatening moments. So the defense of the film such as denial, displacement, intellectualization, projection, rationalization, reaction formation, regression and sublimation. On The Eye movie, it appears a lot of defenses from the major character Sydney. She wants to trace the owner of her eyes and she also wants to get rid of the ghost that always appears on her vision. There are a lot of conflicts appearing coming from outside, between Sydney and the people near her. For example Paul, Paul as a realistic person, he rejects all about the ghost story told by Sydney. This make Sydney be disappointed and the defense of hers appears. Sydney tries to prove that her vision about the ghost is real, by finding the owner of her eyes.